Ketorolac versus Magnesium Sulfate in Migraine Headache Pain Management; a Preliminary Study - Delavar Kasmaei, Hossein; Amiri, Marzieh; Negida, Ahmed; Hajimollarabi, Samaneh; Mahdavi, Nastaransadat (Archives of Academic Emergency Medicine, 2017)
Introduction: Migraine is a common cause of emergency department (ED) visits. To date, there is no recommended drug of choice for pain management of these patients. In the present study, we aimed to evaluate the effectiveness of ketorolac and magnesium sulfate in this regard. Methods: This is a cross-sectional study performed on all 18 - 60 year-old patients, visiting two different EDs with complaint of moderate to severe migraine headache. Patients were treated with 30 mg ketorolac in one hospital and 1 gram magnesium sulfate in the other. Pain scores were assessed on arrival, 1 and 2 hours after drugs administration and quality of pain management was compared between two groups using SPSS 22. Results: 70 patients with the mean age of 36.4 ± 11.4 years were enrolled (51.4% male). The two groups were similar regarding baseline characteristics (p > 0.05). The improvement in pain score in magnesium sulfate group was greater than Ketorolac group after both one hour (6 vs 3; p < 0.001) and two hours (7 vs 5; p < 0.001). Conclusion: It seems that both ketorolac and magnesium sulfate are significantly effective in pain control of patients with migraine headache presenting to the emergency department. Magnesium sulfate was superior to ketorolac both one and two hours after drug administration.